Principles of cross congruence do not apply in naturally disturbed dune slack habitats: Implications for conservation monitoring - Stout, Jane (My University, 2018)
Cross congruence, where diversity or composition of multiple species follow similar patterns, underlies the use of indicator species in conservation practice. However, there are circumstances in which cross congruence has been shown to break down, for example after disturbance events. If cross congruence does not occur in habitats which experience natural disturbance, then conservation measures based on indicator species may yield misleading results. We assessed the degree of cross congruence among three biological taxa in dune slacks, which are temporary ponds found in coastal sand dunes. We also investigated the efficacy of a national monitoring assessment based on a single taxonomic group, plants, to predict the diversity and composition of two other taxonomic groups: snails and water beetles. We found no evidence of cross congruence among these three groups and the plant-based monitoring system did not predict the composition or diversity of snails or water beetles. The potential for dune slacks to support species of conservation interest was demonstrated here as eight snail species and two water beetle species listed as Near threatened or Vulnerable on the Irish Red Lists were found within the 24 sites surveyed, and the Irish populations of two of these are of international significance (Vertigo angustior, Leiostyla anglica). Some of these species of conservation interest were found in dune slacks which were of poor conservation status according to the monitoring methodology applied. Our results show that indicator species drawn from a single taxonomic group are not adequate to monitor the general habitat condition of dune slacks. Dune slacks are among many habitats of conservation interest which experience natural disturbance, and this research has implications for conservation practice in other habitats such as seasonal wetlands and fire-dependent habitats.
PUBLISHED
Keywords: Cross-congruence; Indicator species; Dune slacks; Invertebrates; Snails; Water beetles; Plants; Conservation; Assessment; Smart & Sustainable Planet; BIODIVERSITY; Biodiversity and Conservation; ECOLOGY; Ecological indicators; HABITATS; MONITORING; PLANTS